Structural basis for translocation by AddAB helicase–nuclease and its arrest at χ sites - Krajewski, Wojciech W.; Fu, Xin; Wilkinson, Martin; Cronin, Nora B.; Dillingham, Mark S.; Wigley, Dale B. (Nature (London), 2014)
A dual-function helicase–nuclease, typified by RecBCD in Escherichia coli , acts on free DNA ends during bacterial double-stranded break repair until it reaches a χ sequence at which it pauses before continuing with modified enzymatic properties; here several crystal structures of the related AddAB enzyme from Bacillus subtilis bound to χ-containing DNA are presented, offering insight into χ recognition and its effect on DNA translocation. Taming a rampant nuclease In bacterial double-stranded DNA break repair, the free ends are initially acted upon by a dual function helicase/nuclease, typified by the RecBCD enzyme of Escherichia coli . As RecBCD unwinds DNA, it eventually encounters a polar octameric sequence known as Chi (χ), which causes attenuation and a change in specificity of the nuclease activity. Dale Wigley and colleagues have now solved several structures of AddAB, a related enzyme from Bacillus subtilis , bound to χ-containing DNA. These structures offer insight into the translocation process, the recognition of χ, and the pausing that occurs when χ is recognized. In bacterial cells, processing of double-stranded DNA breaks for repair by homologous recombination is dependent upon the recombination hotspot sequence χ (Chi) 1 , 2 and is catalysed by either an AddAB- or RecBCD-type helicase–nuclease (reviewed in refs 3 , 4 ). These enzyme complexes unwind and digest the DNA duplex from the broken end until they encounter a χ sequence 5 , whereupon they produce a 3′ single-stranded DNA tail onto which they initiate loading of the RecA protein 6 . Consequently, regulation of the AddAB/RecBCD complex by χ is a key control point in DNA repair and other processes involving genetic recombination. Here we report crystal structures of Bacillus subtilis AddAB in complex with different χ-containing DNA substrates either with or without a non-hydrolysable ATP analogue. Comparison of these structures suggests a mechanism for DNA translocation and unwinding, suggests how the enzyme binds specifically to χ sequences, and explains how χ recognition leads to the arrest of AddAB (and RecBCD) translocation that is observed in single-molecule experiments 7 , 8 , 9 .